Chapter 25 Military Strategies for Samhandling in Unforeseen Situations A Historical Perspective - Krabberød, Tommy (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"The purpose of this chapter is twofold. Firstly, a rather paradoxical situation will be discussed. Even though most military practitioners seem to agree on the characteristics of war, two almost diametrically-opposed norms for how to samhandle have arisen: a centralized one and a decentralized one. We argue that the decentralized approach, called Auftragstaktik, is the most effective. In the second part of the chapter we discuss the pedagogical challenge of educating personnel to thrive in a decentralized organization, which must operate effectively in unforeseen and threatening environments. Based on the teachings of Moltke the Elder (1800- 1891) and the much more recent writings of Torgersen, Steiro and Saeverot (2015), we argue that a crucial step in educating for the unforeseen is to give the students the opportunity to solve new problems by themselves, gaining experience that is, as far as possible, self-generated and thereby becoming more aware and confident in dealing with new situations."